一种适用于弹射起飞挂绳回收的小型舰载无人机 (2024)
本发明属于航空飞行器设计技术领域，具体涉及一种适用于弹射起飞挂绳回收的小型舰载无人机，包括机头、机身、机翼、发动机、螺旋桨和平垂尾翼，机头可拆卸连接在机身的前端面上；机身为带边条翼的硬壳体结构，下表面设置有弹射钩，两侧边条翼上安装有机翼；机翼稍部设置有回收钩；发动机安装在机身后端面用以驱动螺旋桨转动提供推力；平垂尾翼通过垂尾尾撑管与机身连接。本发明无人机具有以下优点：结构强度和传力路径优良，满足短距离弹射起飞和无损挂绳回收对于小型无人机的要求；气动性能和飞行稳定性优良，可实现长航时飞行，抗风能力强，适用于海上舰载等复杂场景运行；采用模块化设计，既便于装配和拆卸，又利于装箱存储和运输。 The invention belongs to the technical field of aircraft design and particularly relates to a small ship-borne UAV (unmanned aerial vehicle) applicable to catapult take-off hanging rope recovery. Thesmall ship-borne UAV comprises a head, a body, wings, an engine, propellers and a horizontal and vertical empennage, wherein the head is detachably connected onto the front end surface of the body; the body is of a hard shell structure with strake wings, catapult hooks are arranged on the lower surfaces, and the wings are mounted on the strake wings on the two sides; recovery hooks are arranged atthe tail parts of the wings; the engine is mounted on the rear end surface of the body and used for driving the propellers to rot